The "Spanish" Origins of International Human Rights Law: A Historiographical Review - Boast, Richard P (Victoria University of Wellington Law Review, 2010)
This article critically reviews the claim that the Spanish jurist-theologians Francisco de Vítoria and Bartolomé de las Casas, and their successors, were pioneers of human rights theory and of the law relating to the rights of indigenous peoples. The article seeks to clarify the literature relating to these claims by dividing it into various categories and analysing each in turn. A principal aim of the article is to convey the sheer diversity and scale of the various competing historiographies and the extent to which they stand in contrast to each other. By way of conclusion, there is a discussion of those parts of the debate which are of greatest relevance and resonance for a jurisdiction such as New Zealand, where questions about the origins and nature of indigenous rights law are not merely a matter of theoretical interest, but also of great practical relevance.